Could the eIF2α-Independent Translation Be the Achilles Heel of Cancer? - Holcik, Martin (Frontiers in Oncology, 2015)
Eukaryotic initiation factor eIF2 is a key component of the ternary complex whose role is to deliver initiator tRNA into the ribosome. A variety of stimuli, both physiologic and pathophysiologic activate eIF2 kinases that phosphorylate the α subunit of eIF2, preventing it from forming the ternary complex, thus attenuating cellular protein synthesis. Paradoxically, in cancer cells, the phosphorylation of eIF2α is associated with activation of survival pathways. This review explores the recently emerged novel mechanism of eIF2α-independent translation initiation. This mechanism, which appears to be shared by some RNA viruses and Internal Ribosome Entry Site-containing cellular mRNAs and utilizes auxiliary proteins, such as eIF5B, eIF2D, and MCT-1, is responsible for the selective translation of cancer-associated genes and could represent a weak point amenable to specific targeting for the treatment of cancer.